A BOA-FÉ OBJETIVA, A FUNÇÃO SOCIAL DOS CONTRATOS E A PROTEÇÃO CONTRA OS VÍCIOS REDIBITÓRIOS: TRÊS ELEMENTOS ESTRUTURADORES DOS NEGÓCIOS JURÍDICOS (Reflection and Critique Law Magazine, 2020)
The theoretical analysis carried out in this article focuses on objective good faith, the social function of contracts, and the protection against redibitory vices, studied from different Brazilian legal diplomas. These three elements have undergone numerous transformations over time. These transformations are part of a long process of state legal intervention in individual relations. In current Brazilian law there is a tendency to analyze individuals as having different economic, political and social capacities. This tendency has led to the search for a Justice that is dedicated to fighting for the common good and equity in institutional relations.